2013
DOI: 10.4103/0253-7176.122230
|View full text |Cite
|
Sign up to set email alerts
|

Health status of the prisoners in a central jail of south India

Abstract: Background:Health care in prisons is one of the neglected health areas in our country. Looking into the health problems of prisons will show us a way for the approach in providing the heath care for prisoners.Objectives:To assess the health status of convicted inmates of prison and to study their sociodemographic profile.Materials and Methods:A cross-sectional study was conducted among the inmates of central prison over a period of 1 year. Study population comprised of 300 convicted life-term prisoners. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 8 publications
2
19
1
Order By: Relevance
“…These findings are related to their demographic, social and behavioral characteristics. (3,(10)(11)(12)(13)(14)(15) The low frequency of history of vaccination against hepatitis B was below the expected, considering that the implementation of a vaccination program is a goal of the PNSSP, and an international recommendation. (1,6,16) Low vaccination coverage in prisons and, therefore, the high number of individuals susceptible to infection, are common and confirm the need to ensure access to health services, education programs, and implementation of vaccination programs to prevent HBV infection in prisons.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are related to their demographic, social and behavioral characteristics. (3,(10)(11)(12)(13)(14)(15) The low frequency of history of vaccination against hepatitis B was below the expected, considering that the implementation of a vaccination program is a goal of the PNSSP, and an international recommendation. (1,6,16) Low vaccination coverage in prisons and, therefore, the high number of individuals susceptible to infection, are common and confirm the need to ensure access to health services, education programs, and implementation of vaccination programs to prevent HBV infection in prisons.…”
Section: Discussionmentioning
confidence: 99%
“…The greater number of male custodial deaths world over suggests that male population is much more involved in different kind of criminal activities and consequently to be present in large numbers in jails. According to National Crime Records Bureau, Prison Statics India 2015, out of a total of 1584 deaths in jails reported in the year 2015, only 51 were female inmates and the rest 1533 were male inmates indicating very high custodial male mortality compared to females [14].…”
Section: Discussionmentioning
confidence: 99%
“…Overcrowding has become a serious problem for the correctional administration in India. There are about 1276 prisons with accommodation capacity of 2.8 lakh, however the total number of inmates is around 4 lakh [14]. Overcrowding has serious impacts on prisoners' health.…”
Section: Discussionmentioning
confidence: 99%
“…Wilper et al in 2009 done a study in United States and found that 38.5% of the inmates from federal prisons, 42.8% of the inmates from state prisons and 38.7% of the inmates from local jails are suffering from a chronic medical condition. 9 In 2013 Kumar et al found that 29 inmates suffered from acute upper respiratory tract infections (URI), 15 inmates suffered from acute lower respiratory tract infections (LRI), 54 inmates had ascariasis, 26 inmates had diseases of musculoskeletal system and connective tissue and of 252 inmates had anaemia 10 . Another study done in India by Fotedar et al in 2016 showed that 71.8% of the study population had dental caries and 54.9% of the study inmates had calculus.…”
Section: General Health Status Of the Prisonersmentioning
confidence: 99%